Limitations on Freedom of Expression for the Protection of National Security: A Case Study of Jordan - Ahmed Toubat, Hazem Suleiman; Halim, Rohizan; Mohamed Yusoff, Zuryati (GoDaddy, LLC., 2017)
This paper aims to examine the legal limitations on freedom of expression in Jordanian laws with a view to protect national security. These limitations have been examined in accordance with the controls set forth in international instruments and the Jordanian Constitution. This research used the doctrinal method as a methodology. The primary data were collected through the texts of the Jordanian Constitution and laws, in addition to international and regional instruments. The paper addresses the definition of the concept of national security, the limitations on freedom of expression in order to protect national security in regional and international instruments, and then the controls on these limitations. Finally, the paper examines the legal texts in Jordanian laws that limit freedom of expression in order to protect the security of the Jordanian State. The study concluded that such limitations provided for in the Jordanian laws do not comply with the provisions of international instruments and the Jordanian Constitution. These limitations have been formulated in vague and broad terms that can be interpreted in many ways. The formulation of limitations in this way opens the door to government authorities to violate freedom of expression on the pretext of protecting national security